2020
DOI: 10.7759/cureus.9356
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Primary Percutaneous Coronary Intervention in Patients With a Thrombolysis in Myocardial Infarction Score of Five or Higher

Abstract: Background Primary percutaneous coronary intervention (PCI) is a treatment of choice for patients with STsegment elevation myocardial infarction (STEMI). Of the various risk stratification scores that have been introduced, the thrombolysis in myocardial infarction (TIMI) score is among the most used modalities. Patients with a TIMI score of five or higher are classified as high-risk patients with higher rates of adverse events. Therefore, this study aimed to determine the rate of adverse events after primary P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similarly, in a study by Talreja et al, including 150 patients, 52.7% of the cases were classified as high risk, and 47.3% were at moderate risk. 16 In a study by Iltaf and colleagues, 31.84% of the patients receiving primary PCI had a TIMI risk score of ≥ 9. 17 The study also found that patients with a TIMI score of nine had higher rates of adverse events and complications, including death, stroke, and pulmonary edema, compared to the outcomes of primary PCI that had previously been reported in sizable registry-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study by Talreja et al, including 150 patients, 52.7% of the cases were classified as high risk, and 47.3% were at moderate risk. 16 In a study by Iltaf and colleagues, 31.84% of the patients receiving primary PCI had a TIMI risk score of ≥ 9. 17 The study also found that patients with a TIMI score of nine had higher rates of adverse events and complications, including death, stroke, and pulmonary edema, compared to the outcomes of primary PCI that had previously been reported in sizable registry-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, assessing the risk stratification of each patient, especially after undergoing PPCI is very important. 55 The commonly used tool to assess the success of PCI is the TIMI grade flow. 55 However, the results of this review indicate that only a few studies have reported the results of TIMI of flow post-PPCI.…”
Section: Dovepressmentioning
confidence: 99%
“…55 The commonly used tool to assess the success of PCI is the TIMI grade flow. 55 However, the results of this review indicate that only a few studies have reported the results of TIMI of flow post-PPCI. 13,19,22,23,33 In fact, evaluating the TIMI score after PCI indicates the success of the action, which is closely related to the prognosis and severity of the patient, so it influences LOS.…”
Section: Dovepressmentioning
confidence: 99%
“…The indication of PCI in CAD patient is based on the clinical condition and it is highly recommended in the condition that CAD affect quality of life (Abubakar et al, 2023). Primary PCI is a treatment that given to STEMI patients within 12 hours since the symptoms occur (Talreja et al, 2020). Also, in unstable angina patient, time become very important to conduct PCI in order to prevent MI in the patient.…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%